2020
DOI: 10.1093/ibd/izaa201
|View full text |Cite
|
Sign up to set email alerts
|

The IBD-F Patient Self-Assessment Scale Accurately Depicts the Level of Fatigue and Predicts a Negative Effect on the Quality of Life of Patients With IBD in Clinical Remission

Abstract: Background Fatigue is highly prevalent among patients with inflammatory bowel disease (IBD) and may have an unfavorable impact on quality of life (QoL). The IBD-Fatigue scale (with components SCORE1 and SCORE2) is a recently developed disease-specific questionnaire. We sought to validate a Greek version of IBD-F and use it to assess the severity and characteristics of fatigue and its effect on QoL in our study population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The current study reported abnormal physical fatigue (SFQ ≥ 18) in 51% of IBD patients in well-defined clinical and biochemical remission. These results are comparable with studies from Villoria et al, where 54% of IBD patients in remission were fatigued (based on the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F)), and Varbobitis et al, with a fatigue rate of 46% (IBD-Fatigue scale) [ 30 , 31 ]. In the studies by Williet et al (FACIT-F), Bager et al (Multidimensional Fatigue Inventory (MFI)) and Graff et al (MFI) the prevalence of fatigue was slightly lower: around 26–30% of IBD patients in remission [ 29 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study reported abnormal physical fatigue (SFQ ≥ 18) in 51% of IBD patients in well-defined clinical and biochemical remission. These results are comparable with studies from Villoria et al, where 54% of IBD patients in remission were fatigued (based on the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F)), and Varbobitis et al, with a fatigue rate of 46% (IBD-Fatigue scale) [ 30 , 31 ]. In the studies by Williet et al (FACIT-F), Bager et al (Multidimensional Fatigue Inventory (MFI)) and Graff et al (MFI) the prevalence of fatigue was slightly lower: around 26–30% of IBD patients in remission [ 29 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…In line with the available literature, female sex was one of the main risk factors for fatigue, but a good explanation for this observation has not yet been found [30][31][32]34,35]. The effect of TNF-inhibitors on fatigue is still undetermined.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have investigated the wide spectrum of symptoms, such as lack of energy and poor relationships with food, that affect the physical, emotional, and social realms of CD patient QoL ( 8 , 9 ). A large online cohort study in 2011–2012 conducted through the Crohn's & Colitis Foundation of America reported more depression, anxiety, fatigue, sleep disturbance, pain interference, and social dissatisfaction in a cohort of patients with IBD (∼63% with CD) compared with the general population ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Inflammatory Bowel Disease Fatigue Scale (IBD-F) consists of three sections. Section one measures the severity and frequency of fatigue, section two measures the experience and impact of fatigue on the individual’s life, and section three contains unscored open-ended questions about possible factors contributing to fatigue [ 37 ]. The first two sections are scored on a Likert scale from 0 to 4, and possible total scores are 0–20 in section one and 0–120 in section two.…”
Section: Assessment Of Fatiguementioning
confidence: 99%